HYPERTENSION MANAGEMENT APPROACH THROUGH MODIFIABLE RISK FACTORS IN JEMBER REGION COMMUNITY HEALTH CENTER - Ancah Caesarina Novi Marchianti (UNEJ e-Proceeding)
Hypertension is still on top fifteen of the diseaserank, based on data from the medical record ofpatient visits in Jember Region Community HealthCenter in 2014 (Jember Health Office, 2014).Hypertension is a cardiovascular disease that lead tovarious complications and became one of the maincauses of premature death. Estimated 15 millionpeople suffer from hypertension in Indonesia.National basic medical research in 2013 showed theprevalence of hypertension in Indonesia as much as25.8%. The prevalence was 6 to 15% of adults and50% of them do not realize having a hypertension, sothey tend to be severe hypertension because theyare not avoiding and not knowing the risk factorsand 90% are of essential hypertension. Morbidity inpatients with unknown or undiagnosed hypertensiontend to be higher than morbidity in diagnosedhypertension patients at various health carefacilities. This leads to the prevention of variouscomplications of hypertension, such as stroke,coronary heart disease, and other complications,becomes difficult to be minimized.Risk factors of hypertension can be divided into twowhich are modifiable (physical activity,drinking/eating habit, smoking habit, etc.) and nonmodifiable(gender, age and genetic) risk factors(Adnyani and Sundana, 2014). Numerous attemptsto intervene in the control of hypertension with riskfactors need to be carried out through collaborationbetween the government, especially health workers,and the community. Strategies such as promotiveand preventive efforts in controlling hypertension isan effort to improve the health status of thecommunity.Modifiable risk factors still have many prospects tobe developed to overcome hypertension. Therefore,this study aims to evaluate the management ofhypertension disease through the modifiable riskfactors approach in Jember Region CommunityHealth Center. From the evaluation, we hope toimprove and make more innovation on themanagement approach of hypertension disease inthe future.